Effects of dance and movement therapy on physical ability, flexibility and psychological state for individuals under constant stress - Julija Andrejeva; Asta Mockiene; Dainora Strazdauskaite; Monika Pociene; Grazina Sniepiene; Elvira Malysko; Natalja Istomina; Vaiva Hendrixson (IP Iermakov S.S., 2022)
Background and Study Aim. Dance and movement therapy defined as culturally creative, unique, but at the same time and a universal phenomenon encompassing bodily movements, bodily self - expression, feelings, stories, body interactions with self and others. Aim of the Study was to evaluate the impact of dance and movement therapy on the physical capacity, flexibility and psycho - emotional state of individuals under constant stress. Material and Methods. The study included 18 - 45 years old females (N=20) who has psycho - emotional disorders and came to this facility for rehabilitation treatment procedures.  To assess functional physical capacity was used 6 - minute walk test. For flexibility assessment, to determine the mobility of the lumbar cross section of the spine was used Schober's sample. For psycho - emotional state assessment and for setting the symptoms of depression and anxiety in subjects was used Hospital Anxiety and Depression Symptom (HADS) Scale. The fatigue was measured by Fatigue Impact Scale. Results. Positive statistically significant change in the psycho - emotional state of the subjects was in both groups, however in dance and movement therapy group this state improvement is twice large than in physiotherapy group. The mean values of the HADS scale decreased by 3.1 ± 3.981 points in the first group of subjects treated with physiotherapy and by 6.9 ± 4.62 points in the second group treated with dance and movement therapy. During physical capacity assessment we observe a statistically significant basic change in both groups. In the first study group the average 6 - minute test increased by 35.2 ± 24.89 meters and in the second study group by 27.5 ± 19.44 meters. Conclusions. Dance movement therapy has a positive effect on psycho - emotional state, flexibility and physical ability of people experiencing constant stress. As observed, dance and movement therapy have a positive effect not only on flexibility or physical ability, but also on psycho - emotional state. Dance and movement therapy can be easily applied among different age population. All this makes physiotherapy a highly essential tool to improve person's well - being and quality of life.